Optimization of Glucose from Saccaromycess cerevicae Liquid Waste Using the Acid Hydrolysis Process - Ni Ketut Sari; Dira Ernawati; Komang Nickita Sari (Nusantara Science and Technology Proceedings, 2023)
Selection of Saccharomyces Cereviceae (SC) wastewater as a component produced by PT. Enero comes from a fermentation process that uses SC yeast, it’s availability is great and it has not been used as a raw material for glucose, which until now has been industrial waste. Efforts have been made to convert SC waste water into liquid fertilizer and biodiesel feedstock. The recovery of glucose from SC waste water in the chemical hydrolysis process using the reaction surface method (RSM), the hydrolysis process was carried out with a digital stirrer at a rotation speed of 200 rpm and the addition of 5 ml of 10% NaOH. The variables used were 50–250 mL SC waste water and 10–30 mL HCl volume. The optimization results using RSM of the chemical hydrolysis process are shown in three-dimensional graphs, pH and SC waste water ratio and HCl volume, glucose content and SC waste water ratio and HCl volume. The best results with SC waste volume of 8.58 mL and HCl volume of 34.14 mL achieved a pH of 4.38. In order to achieve a pH of 4.5, a hydrolysis process is carried out because the pH of the SC waste water is very acidic, i.e. 3.5, and 10% NaOH is added to increase the pH. The result of glucose from the hydrolysis process is 17.96%, the required volume of waste water SC of 137.14 ml, the addition of 34.14 ml of HCl as a raw material for the fermentation process. Based on the optimization results using RSM and chemical hydrolysis method, the glucose content is 17.96% and the pH is 4.38 with the SC water waste volume of 137.14 mL and the HCl volume of 34.14 mL.